Empathy and Coping in Allied Health Sciences: Gender Patterns - Dores, Artemisa Rocha (2021)
This study aimed to examine the patterns of associations between empathy and coping among undergraduate men and women studying at Allied Health Sciences. This cross-sectional study is part of a larger longitudinal study conducted in an Allied Health Sciences School. Participants were 183 undergraduate students from 12 training programs (e.g., Physiotherapy, Occupational Therapy, Speech Therapy).